2016
DOI: 10.1111/jabr.12045
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Physical Self‐Concept in Underserved Urban High School Students: Predicting Physical Activity

Abstract: The purpose of this study was to predict physical activity (PA) using multidimensional physical self‐concept theory with underserved urban inner city youth. Eight‐hundred and sixty‐five, mostly African‐American, high school students from a large Midwest inner city participated in the current study. Using structural equation modeling, we found support for multidimensional self‐concept theory. We argue against one‐dimensional models of self‐esteem as two discrete physical self‐concepts accounted for significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
3
0
1
Order By: Relevance
“…Because the sample of the present study is composed by people with low to moderate ED severity, it is possible that global self-esteem is less influenced by specific physical self-perceptions than in patients with ED with severe to extreme severity. Our results are consistent with Martin et al’s ( Martin et al, 2016 ) who found that sport competence and physical condition were the only two significant contributors to the variance of amount of exercise in general population. According to the Monthuy-Blanc et al’s study ( Monthuy-Blanc et al, 2012 ) on the directionality of the relationships between global self-esteem and physical self dimensions in outpatients’ girls with anorexia, global self-esteem of severe patients may be directly influenced by physical self-perceptions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Because the sample of the present study is composed by people with low to moderate ED severity, it is possible that global self-esteem is less influenced by specific physical self-perceptions than in patients with ED with severe to extreme severity. Our results are consistent with Martin et al’s ( Martin et al, 2016 ) who found that sport competence and physical condition were the only two significant contributors to the variance of amount of exercise in general population. According to the Monthuy-Blanc et al’s study ( Monthuy-Blanc et al, 2012 ) on the directionality of the relationships between global self-esteem and physical self dimensions in outpatients’ girls with anorexia, global self-esteem of severe patients may be directly influenced by physical self-perceptions.…”
Section: Discussionsupporting
confidence: 93%
“…Even though physical activity and exercise are related to global well-being in the general population ( Hausenblas and Fallon, 2006 ; Martin et al, 2016 ), its effects can become particularly deleterious in ED ( Hausenblas et al, 2008 ). Indeed, patients with ED who engage in EE show more severe psychopathology, longer duration of treatment, hospitalizations characterized by multiple readmissions, lower Body Mass Index [BMI (kg/m 2 )] than those who do not, and are more likely to relapse ( Solenberger, 2001 ; Steinhausen et al, 2008 ; Bratland-Sanda et al, 2010 ; Vall and Wade, 2017 ; Young et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients with eating disorders tend to overexert themselves in terms of exercise amount, frequency, or both [ 42 ]. Although physical activity is associated with health, in the case of eating disorders, it can carry greater losses [ 43 ]. In a study of 61 female triathletes, Elbourne et al found a significant positive correlation between mandatory exercise and eating disorders [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…iziksel benlik algısı, fiziksel aktivite ve spora katılımın artırılması, depresyon riskinin azaltılması ve fiziksel uygunluğun geliştirilmesi üzerindeki olumlu etkilerinden dolayı araştırmacılar tarafından son yıllarda sıklıkla ele alınan bir kavramdır. [1][2][3][4] Araştırmacılar, fiziksel benlik algısının adölesan ve çocuklarda tutum bozukluğu, travma sonrası stres bozukluğu, anoreksiya nervoza, depresyon ve anksiyete gibi psikiyatrik rahatsızlıkların başlaması ve devamlılığında önemli bir etken olduğunu ortaya koymuştur. [5][6][7][8] Olumlu fiziksel benlik algısı, beden imajının geliştirilmesi, fiziksel aktivitelerden daha fazla keyif alınması ve sedanter davranışların azaltılmasında psikolojik ve fiziksel açıdan önemlidir.…”
unclassified